105k views
0 votes
Let S be the sphere of radius 1 centered at (2, 4, 6). Find the distance from S to the plane x + y + z = 0.

1 Answer

3 votes

Answer:

5.928

Explanation:

Given that:

The relation of the plane x+y+z= 0

Suppose (x,y,z) is any point on the plane.

Then the difference between (2,4,6) to (x,y,z) is:


d^2 = (x-2)^2 + (y -4)^2 + ( z -6)^2 \\ \\ d^2 = (x^2 -4x+4) + ( y^2-8y +16) +(z^2 -12z + 36)


d^2 = x^2 + y^2 +z^2 -4x -8y -12z +4 +16 +36


d^2 = x^2 +y^2 + z^2 -4x -8y -12z +56


f(x,y,z) =d^2 = x^2 + y^2 + z^2 - 4x -8y - 12 z +56 - - - (1)

To estimate the maximum and minimum values of the function f(x,y,z) subject to the constraint g(x,y,z) = x+y+z =0

By applying Lagrane multipliers;

If we differentiate equation (1) with respect to x; we have:

f(x,y,z) = 2x -4

If we differentiate equation (1) with respect to y; we have:

f(x,y,z) = 2y - 8

If we differentiate equation (1) with respect to z; we have:

f(x,y,z) = 2z - 12

Differentiating g(x,y,z) with respect to x, we have:


g_x(x,y,z) = 1

Differentiating g(x,y,z) with respect to y, we have:


g_y(x,y,z) = 1

Differentiating g(x,y,z) with respect to z, we have:


g_z(x,y,z) = 1

Calculating the equations
\bigtriangledown f = \lambda \bigtriangleup g \ \ \ \& \ \ \ g(x,y,z) =0


f_x = \lambda g_x\\


2x - 4 = \lambda (1)


2x= 4 + \lambda


x= 2 + (\lambda )/(2) --- (2)


f_y = \lambda g_y


2x -8 = \lambda(1)


2x = 8+ \lambda


x = 4+(\lambda)/(2) --- (3)


f_z = \lambda g_z


2x -12 = \lambda (1)


x = 6 + (\lambda )/(2) --- (4)

x+y+z = 0 - - - (5)

replacing x, y, z values in the given constraint

x + y + z = 0


2+(\lambda)/(2)+4+(\lambda)/(2)+6+(\lambda)/(2)=0


12 + (3 \lambda )/(2)=0


(3 \lambda )/(2)=-12


3 \lambda=-12 * 2


3 \lambda=-24


\lambda=(-24)/(3)


\lambda=-8

Therefore, from equation (2)


x=2 +( \lambda )/(2)


x=2 +( -8 )/(2)

x = 2 - 4

x = - 2

From equation (3)


x=4 +( \lambda )/(2)


x=4 +( -8 )/(2)

x = 4 - 4

x = 0

From equation (3)


x=6 +( \lambda )/(2)


x=6 +( -8 )/(2)

x = 6 -4

x = 2

i.e (x,y,z) = (-2, 0, 2)


d^2 = (x-2)^2 +(y-4)^2 + (z -6)^2


d^2 = (-2-2)^2 +(0-4)^2 + (2 -6)^2


d^2 = 16 +16 + 16


d^2 =48


d =√(48)


d= \pm 6.928

since we are taking only the positive integer because distance cannot be negative, then:

The distance from the center of the sphere to the plane is 6.928.

However, the distance from the surface S to the plane is:

6.928 - radius of the sphere.

where;

the radius of the sphere is given as 1

Then:

the distance from the surface S to the plane is:

6.928 - 1

= 5.928

User Juljan
by
5.2k points